Permeability of porous ceramic based on calcium carbonate as pore generating agent. Issue 3 (April 2015) - Simão, L.; Caldato, R.F.; Innocentini, M.D.M.; Montedo, O.R.K.
Abstract: This study concerns the processing and characterization of porous ceramics based on low cost mineral raw materials for environmental applications. Three formulations were tested with calcium carbonate as pore generating agent and different proportions of kaolin, potassic feldspar, albite, quartz and white clay. Ceramic bodies were formed by pressing, heat treated up to 1180 °C and characterized for porosity, flexural strength, air permeability and microstructural aspects. The resulting bodies displayed apparent porosity (28–32%), flexural strength (7–29 MPa), permeability coefficients ( k 1 ≅10 −15 m 2 and k 2 ≅10 −11 m) and average pore size (0.706–1.137 μm) suitable for membrane separations. The formulation containing 50% kaolin, 20% limestone, 10% potassic feldspar, 10% albite and 10% quartz (dry basis) was considered the most suitable for separation of suspended solids from liquid suspensions (microfiltration).